Pengaruh dan Metode Pensyarahan Hadis Sayyid Muhammad Ibn Alawi al-Maliki - Muhid, Muhid; Roziqin, Muhammad Khoirur; Nurita, Andris (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
This paper aims to reveal the method of presenting Sayyid Muḥammad's hadith which is used as an argument to reject Wahhabi teachings by using several methods that are needed such as Tahlili, Ijmali, Mauḍu`i and Muqaran Sayyid Muḥammad can provide rebuttals to the Wahhabi opinion. Based on this description, this research is a literature review using a descriptive analysis model as the method that we will use in this paper, for completeness of the data we use a sample of three hadiths, namely the hadith about visiting the Prophet's mosque, charity that is beneficial to people who have died and doing good for the neighbors with the hadith sample found an illustration of Sayyid Muḥammad's style of reciting hadith, which in the end resulted in his comments and explanations which later greatly influenced the understanding of Ahlu Al-Sunnah.